(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article analyzes the features of the implementation of managerial decisions in government bodies in terms of the control and responsibility function; reveals the essence of managerial decision-making in government structures, the conditionality of the regulatory framework, comprehensive objectivity and validity; highlights criteria for evaluating the effectiveness of managerial decision execution; determines the sequence of control measures in government.